A study of the solid earth tides, ocean and atmospheric loadings using an 8-year record (2010–2018) from superconducting gravimeter OSG-060 at Djougou (Benin, West Africa). (February 2020) - Hinderer, Jacques; Riccardi, U.; Rosat, S.; Boy, J.-P.; Hector, B.; Calvo, M.; Littel, F.; Bernard, J.-D.
Abstract: We investigate a nearly 8-year record (2010–2018) of the superconducting gravimeter OSG-060 located at Djougou (Benin, West Africa). We first perform a tidal analysis with ET34-ANA v7.1 software that leads to the gravimetric amplitude and phase factors for all separable waves according to the available time duration. We test nine different ocean tide models for the main eleven tidal constituents (Ssa, Mm, Mf, Q1, O1, P1, K1, N2, M2, S2, K2). After correction for ocean tidal loading we obtain the real and imaginary parts of the residual vector. We also investigate atmospheric loading which is dominated in this equatorial location by the thermal waves S1 and S2 that are modulated in amplitude by annual and semi-annual components. After correction for ocean loading, we test different air pressure corrections on the tidal gravimetric factors for the waves Sa, Ssa, S1 and S2. We show the rather large discrepancy that exists between the classical single admittance pressure reduction and a hybrid model using global atmospheric models everywhere except in the local zone where the model pressure is replaced by the observed pressure.